The detection of SARS-CoV-2 RNA in indoor air of dental clinics during the COVID-19 pandemic - Bazzazpour, Shahriyar (Environ Sci Pollut Res Int, 2021)
In the indoor environment of dental clinics, dental personnel and patients are exposed to a risk of infection because of the transmission of SARS-CoV-2 via particles or droplets. This study investigated the presence of SARS-CoV-2 RNA in indoor air of dental clinics in Tehran, Iran. Air sampling was done (n = 36) collecting particulate samples on PTFE filters at flow rates of 30 to 58 L/min. The samples were analyzed with novel coronavirus nucleic acid diagnostic real-time PCR kits. Only 13 out of 36 samples were positive for SARS-CoV-2 RNA. Logistic regression showed that sampling site’s volume, PM(2.5) concentration, number of people, and number of active patient treatment units were significantly positively related with the presence of SARS-CoV-2 RNA. Thus, strategies to control the spread of COVID-19 should include reducing the number of infected people in dental clinics, adding filtration systems, and/or improving ventilation conditions.